Economic efficiency estimation from introduction of technology of biscuits with xampan usage - Черевична, Наталія Іванівна; Самохвалова, Ольга Володимирівна; Смольнякова, Наталія Миколаївна (Eastern-European Journal of Enterprise Technologies, 2012)
The question of estimation of efficiency of development and introduction of new technology of sponge semi-finished products is considered on condition of the use stabilizator of microbal origin